Survival Outcome with Routine Clinical Use of 82Rb PET/CT Myocardial Blood Flow (MBF) Quantification. (20th July 2021) - Wan, S; Speechly-Dick, ME; Menezes, LJ; Endozo, R; Bell, R; Walker, M; Ganeshan, B; Dickson, J; Kayani, I; Groves, AM
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): NIHR Biomedical Research Centre, University College London Hospitals Background: The prognostic value of 82Rb PET/CT derived myocardial blood flow (MBF) is increasingly recognised in both general and specific cardiovascular populations. Purpose: This study investigates the prognostic potential of MBF in a large cohort of patients undergoing routine 82Rb PET/CT examination. Methods: 1148 consecutive patients (687 males, mean age 64 +/- 12 years) whom had been referred for 82Rb PET/CT examination in a single centre were included in this study. All patients completed a stress 82Rb PET/CT with adenosine infusion, paired with a rest study. Dynamic PET acquisitions were performed in both. Cardiovascular risk factors were documented as per clinical routine. Images were checked for quality and analysed using a proprietary software by an experienced operator to derive MBF parameters. Overall survival was recorded following the study. Results: Median follow-up period was 71 +/- 28 months. Mean survival was 121 (95% CI: 118-124) months. On univariate analysis, global myocardial flow reserve <1.77 was associated with a higher all-cause mortality (p < 0.001). Other parameters including higher age (> =76 years), lower BMI (<21), qualitative abnormality on the myocardial perfusion scan (MPS), low hyperaemic ejection fraction on the gated studies (stress < 37 and rest < 34). Patients being on cardiac glycosides and diuretics were also significant predictor of poor prognosis (p < 0.001) on univariate analysis, presumably reflecting underlying arrhythmia and heart failure. A multivariate Cox regression analysis (step-wise Forward Wald), comprising of the above significant univariate markers, highlighted global myocardial flow reserve (HR: 2.6, 95%CI: 1.8-3.6, p < 0.001), age (HR: 2.8, 95%CI: 2.0-3.9, p < 0.001), , BMI (HR: 2.7, 95%CI: 1.7-4.1, p < 0.001), , ejection fraction (stress - HR: 3.3, 95%CI: 2.3-4.8, p < 0.001), MPS (HR: 1.5, 95%CI: 1.1-2.1, p = 0.024), and patients on diuretics (HR: 1.8, 95%CI: 1.2-2.5, p = 0.003) were independent predictors of overall survival (overall model: p < 0.001) Discussion: We show that high volume routinely derived MBF in patients undergoing 82Rb PET/CT is a strong predictor of mortality and independent of other risk factors. This has important clinical implication for measuring not only interventional treatment but also measuring the effect of lifestyle and medical strategies.